2022
DOI: 10.1007/s00405-021-07245-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency reallocation based on cochlear place frequencies in cochlear implants: a pilot study

Abstract: Purpose The aim of this study is to evaluate speech perception outcomes after a frequency reallocation performed through the creation of an anatomically based map obtained with Otoplan®, a tablet-based software that allows the cochlear duct length to be calculated starting from CT images. Methods Ten postlingually deafened patients who underwent cochlear implantation with MED-EL company devices from 2015 to 2019 in the Tertiary referral center University H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Both experimental maps performed worse than the clinical map. Recently, a pilot study was published which evaluated a software-based anatomy based fitting procedure in subjects with a CI from MED-EL ( Di Maro et al, 2022 ). Here, based on post-operative CT scans, mismatch was minimized within the 950–3,500 Hz region while mismatch at low and high frequencies was tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both experimental maps performed worse than the clinical map. Recently, a pilot study was published which evaluated a software-based anatomy based fitting procedure in subjects with a CI from MED-EL ( Di Maro et al, 2022 ). Here, based on post-operative CT scans, mismatch was minimized within the 950–3,500 Hz region while mismatch at low and high frequencies was tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…Speech recognition deteriorated with the experimental settings, despite a 3 month habituation period. Recently, a pilot study was performed in which implanted subjects showed better results on speech discrimination tests with an anatomically based FAT compared to their routine clinical settings ( Di Maro et al, 2022 ). Other strategies to improve CI frequency distributions have also been evaluated, such as evolutionary algorithms and smartphone applications which enable FAT self-adjustment by patients ( Fu et al, 2002 ; Jethanamest et al, 2017 ; Saadoun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomy-based fitting (ABF) is a technique that allows the specific frequency of neural elements to be matched to the frequency assigned to each contact. This can reduce the adaptation time and enhance speech perception and discrimination (12). To perform a proper ABF, it is necessary to identify the position of the inserted electrode and accurately measure the angular insertion depth (AID) of the electrodes (12).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is called anatomy-based fitting (ABF) with the aim to reduce the frequency to place mismatch. To our knowledge, only one investigation has attempted to apply ABF using the aforementioned clinical fitting software (7), without further modifications from the manufacturer. However, based on the before experience from our clinic, we found the "as is" application of ABF as implemented by the manufacturer unsuccessful because the lowest frequency band is too large; hence, patients did not accept the sound quality.…”
Section: Introductionmentioning
confidence: 99%